The Effect Of Entrepreneurship Orientation, Management Capabilities and Image Difference On Sme’s Competitive Advantage - Dhimas Aziz Nugroho; Rochiyati Murniningsih; Dahli Suhaeli (Prosiding University Research Colloquium, 2022)
This study aims to examine whether entrepreneurial orientation, management ability and image differentiation have an effect on competitive advantage. The sample used in this study is business actors in Food and Beverage SMEs in Magelang Regency. The sampling technique used in this research is purposive sampling with 96 respondents. This research method uses descriptive quantitative. Data processing was tested using multiple linear regression test. The results of this study indicate that the entrepreneurial orientation variable, management ability and image differentiation simultaneously have a positive effect on competitive advantage, the entrepreneurial orientation variable partially has a positive effect on competitive advantage, the management ability variable partially has a positive effect on competitive advantage, and partial image differentiation has a positive effect. positive for competitive advantage.